2013
DOI: 10.1371/journal.pone.0060367
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Programmed Cell Death Ligand-1 (PD-L1/CD274) in the Development of Graft versus Host Disease

Abstract: Programmed cell death ligand-1 (PD-L1/CD274) is an immunomodulatory molecule involved in cancer and complications of bone marrow transplantation, such as graft rejection and graft-versus-host disease. The present study was designed to assess the dynamic expression of this molecule after hematopoietic stem cell transplantation in relation to acute graft-versus-host disease. Female BALB/c mice were conditioned with busulfan and cyclophosphamide and transplanted with either syngeneic or allogeneic (male C57BL/6 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 38 publications
1
7
0
Order By: Relevance
“…Strong differences were, however, observed in the expression of PD-1 ligands that were highly upregulated in lymph nodes but not in the liver. Interestingly, we observed that PD-1 ligands were upregulated by both hematopoietic APCs and stromal cells in lymph nodes, in accordance with the idea that organ parenchyma contributes to engage the PD-1 axis (Schilbach et al, 2007;Al-Chaqmaqchi et al, 2013). Consistently, blockade of PD-1/PD-1-ligand interactions during allo-HSCT selectively increased CTL activity in lymph nodes.…”
Section: Discussionsupporting
confidence: 88%
“…Strong differences were, however, observed in the expression of PD-1 ligands that were highly upregulated in lymph nodes but not in the liver. Interestingly, we observed that PD-1 ligands were upregulated by both hematopoietic APCs and stromal cells in lymph nodes, in accordance with the idea that organ parenchyma contributes to engage the PD-1 axis (Schilbach et al, 2007;Al-Chaqmaqchi et al, 2013). Consistently, blockade of PD-1/PD-1-ligand interactions during allo-HSCT selectively increased CTL activity in lymph nodes.…”
Section: Discussionsupporting
confidence: 88%
“…Its efficacy is reinforced when it is combined with the bifunctional DNA-alkylating drug busulfan. In an experimental study in mice transplanted with allogeneic bone marrow cells (model of acute graft-versus-host disease), the alkyl sulfonate busulfan was also found to enhance the expression of PD-L1 in the target organs ( 87 ).…”
Section: Dna-alkylating Drugsmentioning
confidence: 99%
“…Programmed cell death (PCD) is an intrinsic mechanism that all cells are capable of executing, leading to loss of cells that either pose a danger to the organism such as activated T cells or cells sacrificed during tissue remodeling [41]. Such death pathways can also be triggered by stresses.…”
Section: Hsps and The Defining Traits Of Cancer Cellsmentioning
confidence: 99%